Lithium ion battery negative electrode material and preparation method and application thereof
By using a combination of nanosilicon/graphene precursor composite and lithium salt in the lithium-ion battery anode material, and through lithium silicate coating treatment, the problem of insufficient volume expansion and conductivity of the lithium-ion battery anode material during charging and discharging is solved, and a silicon-carbon anode material with long cycle life and high rate performance is achieved.
Patent Information
- Application Number
- CN202311234851.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
The volume expansion of the negative electrode material of the existing lithium-ion battery during charging and discharging causes the electrode sheet to fall off or crack, have poor cycle life, and insufficient conductivity, which affects the performance of high specific capacity.
By mixing the graphene powder with the nano-silicon dispersion, a nano-silicon/graphene precursor composite is formed, and grinding and calcining is performed with the lithium salt to form a composite coated with lithium silicate on the surface of the nano-silicon, and then mixed with asphalt to carbonize and sinter to obtain a nano-silicon/graphene silicon silicon-carbon composite negative electrode material coated with lithium silicate.
The silicon-carbon negative electrode material that achieves long cycle life and high rate performance eases the impact of volume expansion on the SEI film through the combination of hollow structure and silicate layer, and improves the conductivity and cyclic stability.
Smart Images

Figure HDA0004465327590000011 
Figure HDA0004465327590000012 
Figure HDA0004465327590000021
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode material for lithium-ion batteries and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries mainly use graphite materials as negative electrode active materials, and their theoretical capacity is only 372mAh / g, which cannot meet the requirements of new energy vehicles for high-performance lithium-ion batteries. The theoretical capacity of silicon is 4200mAh / g, which is ten times the capacity of graphite negative electrode. In addition, silicon is cheap and easy to obtain, has a friendly processing environment, and has a low lithium insertion potential, so it has received widespread attention and research. However, the large volume expansion of silicon materials during the charging and discharging process can easily cause the pole pieces to fall off or crack, resulting in a poor cycle life of lithium batteries. At the same time, the poor conductivity of silicon materials themselves also affects the performance of their high specific capacity. In order to further reduce the volume expansion of silicon and improve its conductivity, more feasible methods include preparing nano-scale silicon particles, which can reduce the impact of volume expansion. In addition, nano-silicon is compounded with carbon materials to prepare silicon-carbon composite negative electrode materials, which can not only improve the conductivity of silicon, but also fully reduce the impact of volume expansion.
[0003] CN114068891A discloses a composite of carbon materials such as graphene and carbon nanotubes with nano-silicon of different hardness to reduce the impact of silicon volume expansion, and the obtained silicon-carbon specific capacity can reach 532mAh / g, the first efficiency is 92%, and the capacity retention rate is 96.5% after 100 cycles. However, there is no sufficient buffer space for the volume change of nano-silicon during charging and discharging.
[0004] CN112751011B discloses a method in which silicon dioxide is used as an active material, the surface is coated with magnesium oxide and silicate, and then a carbon layer is coated by CVD. The obtained silicon-carbon negative electrode has a specific capacity of 1414 mAh / g, an initial efficiency of 91.3%, and a capacity retention rate of about 98% after 50 cycles. The conductivity is improved by carbon deposition, and the conductivity of the prepared silicon-carbon negative electrode is poor.
[0005] CN110112380B functionalizes the surface of nano-silicon and graphene, forms a nano-silicon / graphene composite through electrostatic force, and obtains a silicon-carbon negative electrode through processes such as spray granulation. The specific capacity is 1250mAh / g, the first efficiency is 84%, and the 100-week capacity retention rate is 83%. However, it does not consider the adverse effects of the oxide layer on the surface of nano-silicon on the performance of silicon-carbon.
[0006] CN111435736B adopts graphene oxide and nano-silicon mixed, spray dried to obtain a composite, and then mixed with an organic carbon source liquid phase and spray dried to obtain a nano-silicon graphene composite silicon carbon coated with an outer shell carbon layer, with a specific capacity of 1885 mAh / g and an initial efficiency of 82.7%. However, graphene oxide has many defects and its conductivity is poor. Summary of the invention
[0007] In view of this, the main purpose of the present application is to provide a lithium-ion battery negative electrode material and a preparation method and application thereof, so as to obtain a silicon-carbon negative electrode material with long cycle life and high rate performance.
[0008] To achieve the above-mentioned purpose of the invention, the first aspect of the present application provides a method for preparing a negative electrode material for a lithium-ion battery, comprising the following steps:
[0009] 1) mixing graphene powder and nano-silicon dispersion to obtain a mixed solution;
[0010] 2) heating the mixed solution to remove the solvent to obtain a nano-silicon / graphene precursor composite;
[0011] 3) mixing the nano-silicon / graphene precursor composite with a lithium salt and grinding them to obtain a mixture;
[0012] 4) calcining the mixture to obtain a composite material in which the surface of nano-silicon is coated with lithium silicate;
[0013] 5) The composite material in step 4) is mixed with asphalt and then carbonized and sintered to obtain a nano-silicon / graphene silicon-carbon composite negative electrode material coated with lithium silicate.
[0014] Furthermore, in step 1), the mixing comprises: mixing the nano-silicon dispersion and the graphene powder in a solvent, preferably by sand grinding; and / or,
[0015] The solvent is selected from one or more of alcohols, methyl pyrrolidone and acetone, and the alcohol solvent is selected from one or more of ethanol, isopropanol and butanol; and / or,
[0016] A carbon source is also added to the solvent, and the carbon source is selected from a mixture of one or more of glucose, sucrose, polyvinyl pyrrolidone (PVP), and carboxymethyl cellulose. Preferably, the carbon source accounts for 5-40% of the mass of the graphene powder and the nano-silicon dispersion.
[0017] Furthermore, in step 2), the heating is performed in a vacuum state at 40-65° C. Preferably, in step 2), the step further comprises drying the nano-silicon / graphene precursor composite.
[0018] Furthermore, in step 3), the lithium salt is selected from one or more of lithium carbonate and lithium acetate.
[0019] Furthermore, in step 3), the lithium salt accounts for 0.2-1% of the mass of the nano-silicon / graphene precursor composite.
[0020] Furthermore, in step 3), the grinding is ball milling, and the ball milling time is preferably 20-40 min.
[0021] Furthermore, in step 4), the calcination treatment conditions include: sintering for 3-12 hours in an inert atmosphere at 330-700°C.
[0022] Furthermore, in step 5), the composite and the asphalt are mixed in a mass ratio of 85:15-98:2, preferably by ball milling.
[0023] Furthermore, in step 5), the carbonization sintering conditions include: sintering for 1-5 hours in an inert atmosphere at 800-1200°C.
[0024] The second aspect of the present invention provides a negative electrode material for a lithium ion battery prepared by the above preparation method.
[0025] The third aspect of the present invention provides an application of a negative electrode material for a lithium ion battery, which is used to manufacture a lithium ion battery.
[0026] Compared with the prior art, this application has the following advantages:
[0027] The present invention mixes graphene powder with nano-silicon dispersion to obtain a mixed solution; heats the mixed solution to remove the solvent, and solid-phase granulates the mixed solution through the above steps to obtain a three-dimensional nano-silicon / graphene precursor composite with a hollow structure, which provides sufficient buffer space for the volume expansion of the nano-silicon during the charge and discharge process. In addition, since the hollow structure is inside the particles and the SEI film is formed outside the particles, the effect of silicon volume expansion on the stability of the SEI film can be reduced, which is beneficial to the improvement of silicon-carbon cycle performance. At the same time, the present invention grinds the nano-silicon / graphene precursor composite with lithium salt and calcines it to obtain a nano-silicon surface coated with lithium silicate. Salt complex, wherein the silicon oxide layer on the surface of nano-silicon reacts with lithium salt to obtain a silicate layer-coated nano-silicon with a stable structure, the silicate layer is beneficial to lithium ion transmission, and is beneficial to the improvement of silicon-carbon negative cycle stability and rate performance; then the complex is carbonized and sintered with asphalt to obtain a lithium silicate-coated nano-silicon / graphene silicon-carbon composite negative electrode material; the application provides an innovative solution for the development of silicon-carbon negative electrode materials with long cycle life and high rate performance, and compared with the traditional silicon-carbon spray drying granulation technology, the preparation method of the application has the advantages of high efficiency, low energy consumption and easy industrialization.
[0028] Other features and advantages of the present application will be described in detail through the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the lithium silicate@silicon / graphene composite silicon-carbon negative electrode material prepared in Example 2 of the present invention and the corresponding EDS spectra of carbon and silicon elements (arranged from left to right).
[0030] Figure 2 This is a cross-sectional cutout and a partial enlarged view (arranged from left to right) of the lithium silicate@silicon / graphene composite silicon-carbon negative electrode material prepared in Example 2 of the present invention.
[0031] Figure 3 This is the XPS spectrum of Si and Li elements in the lithium silicate@silicon / graphene composite silicon-carbon negative electrode material prepared in Example 2 of the present invention (arranged from left to right).
[0032] Figure 4 This is the XRD data diagram of the silicate@silicon / graphene composite silicon-carbon negative electrode material prepared in Example 2 of the present invention and the Li2Si2O3 peak PDF#40-0376.
[0033] Figure 5 This is a comparison chart of the rate performance of various composite silicon-carbon negative electrode materials prepared in Example 2 of the present invention, and Comparative Example 1 and Comparative Example 2.
[0034] Figure 6 Schematic diagram of the power-off cycle of the lithium silicate@silicon / graphene composite silicon-carbon negative electrode material prepared in Example 2 of the present invention (1C / 1C). DETAILED DESCRIPTION
[0035] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0036] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0037] The sources and conditions of the main raw materials in the embodiments and comparative examples are described as follows:
[0038] Graphene powder (Qingdao Haoxin HX-G), nano-silicon dispersion (120-150nm silicon dispersion, prepared by sand-milling micron silicon), lithium salt (Sinopharm), asphalt (Dalian Mingde), lithium battery graphite negative electrode (Comparative Example 2, Shanshan Technology, FSN-1).
[0039] The first aspect of the present application provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0040] 1) mixing graphene powder and nano-silicon dispersion to obtain a mixed solution;
[0041] 2) heating the mixed solution to remove the solvent to obtain a nano-silicon / graphene precursor composite;
[0042] 3) mixing the nano-silicon / graphene precursor composite with a lithium salt and grinding them to obtain a mixture;
[0043] 4) calcining the mixture to obtain a composite material in which the surface of nano-silicon is coated with lithium silicate;
[0044] 5) The composite is mixed with asphalt and then carbonized and sintered to obtain a lithium silicate-coated nano-silicon / graphene silicon-carbon composite negative electrode material.
[0045] In the present application, in step 1), nano-silicon and graphene powder are compounded to obtain a composite lamellar structure, and then the composite lamellar structure is solid-phase granulated in step 2) to form a three-dimensional nano-silicon / graphene precursor complex. The three-dimensional complex constructed by the lamellar structure has a large hollow structure inside, which can play a role in improving the electrochemical performance of the silicon-carbon negative electrode.
[0046] Preferably, the particle size of the graphene powder is 5-10 μm, preferably 8-10 μm.
[0047] Preferably, in step 1), the mixing comprises: mixing the nano-silicon dispersion and the graphene powder in a solvent, preferably mixing by sand grinding. The solvent is selected from one or more of alcohols, methyl pyrrolidone (NMP) and acetone.
[0048] In some examples, the alcohol solvent is selected from one or more of ethanol, isopropanol, and butanol.
[0049] In some examples, the sand milling mixing is: mixing materials such as nano-silicon dispersion, graphene powder, and solvent, and then placing them in a sand mill for sand milling, so that the materials are dispersed more evenly.
[0050] In some examples, a carbon source is further added to the solvent, and the carbon source is selected from a mixture of one or more of glucose, sucrose, polyvinyl pyrrolidone (PVP), and carboxymethyl cellulose, so that the carbon source coats the surface of the nano-silicon. Preferably, the carbon source accounts for 5-40% of the mass of the graphene powder and the nano-silicon dispersion, and is exemplarily 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.
[0051] Preferably, in step 2), the heating is performed at 40-65° C. under vacuum to recover the solvent and obtain a solid.
[0052] In some examples, step 2) further includes drying the solid obtained after solvent recovery, for example, drying in a vacuum drying oven at 60-90° C. for 6-12 hours.
[0053] Preferably, in step 3), the lithium salt is selected from one or more of lithium carbonate and lithium acetate.
[0054] Preferably, in step 3), the lithium salt accounts for 0.2-1% of the mass of the nano-silicon / graphene precursor composite, exemplarily 0.2%, 0.6%, 1%. Too little lithium salt will result in insufficient lithium silicate formed on the surface of the nano-silicon, while too much lithium salt will produce other types of lithium silicate compounds.
[0055] Preferably, in step 3), the grinding is ball milling, and the ball milling time is preferably 20-40 min, exemplarily 20 min, 30 min, 40 min. If the ball milling time is too short, the granulation effect cannot be achieved, and if the time is too long, the micron particle structure will be destroyed; the ball milling medium can be selected from 0.2-1.2 mm size zirconium beads.
[0056] Preferably, in step 4), the calcination treatment conditions include: sintering for 3-12 hours at 330-700° C. in an inert atmosphere. In some examples, the inert atmosphere is nitrogen. The reaction is suitable under the above parameter conditions. If the temperature is too high, the lithium silicate salt will decompose.
[0057] Preferably, in step 5), the composite and asphalt are ground and mixed, preferably ball-milled; in some examples, the composite and asphalt are mixed in a mass ratio of 85:15-90:10. The role of asphalt is to coat the micron particles with a carbon layer, which plays a role in isolating the electrolyte and maintaining the structural stability of the micron particles.
[0058] Preferably, in step 5), the carbonization sintering conditions include: sintering for 1-5 hours in an inert atmosphere at 800-1200° C. In some examples, the inert atmosphere is nitrogen.
[0059] The second aspect of the present invention provides a negative electrode material for a lithium ion battery prepared by the above preparation method.
[0060] The third aspect of the present invention provides an application of a negative electrode material for a lithium ion battery, which is used to manufacture a lithium ion battery.
[0061] The following examples are used to illustrate the lithium-ion battery negative electrode material of the present application and its preparation and application.
[0062] The negative electrode materials prepared in the following examples and comparative examples were mixed with conductive carbon black Super P and binder polyvinylidene fluoride (PVDF) in a mass ratio of 92:3:5, and solvent N-methylpyrrolidone (NMP) was added to stir to form a uniform negative electrode slurry. The negative electrode slurry was evenly coated on an aluminum foil with a scraper and dried to obtain a negative electrode sheet. After cutting, the sheet was transferred to an MBraun2000 glove box (Ar atmosphere, H2O and O2 concentrations less than 0.1×10 6 Volume %), a metal lithium sheet was used as a reference electrode, and a button cell was assembled. The electrochemical properties of the button cell, such as rate performance and cycle performance, were tested.
[0063] The electrochemical performance test method is as follows:
[0064] a. The charge and discharge capacity and the first coulombic efficiency of the battery were tested by the battery test system CT2001A battery tester of Wuhan Blue Electric Electronics Co., Ltd., with a current of 0.1C (1C = 350mAh / g) and a voltage of 0.3V.
[0065] b. 2C continuous high rate cycle charge and discharge test was carried out by Xinwei battery tester. Test conditions: at room temperature, 2C constant current to constant voltage charging to 4.2V, cut-off current 0.05C, 2C constant current discharge to 2.5V.
[0066] Example 1
[0067] Nano-silicon dispersion (130nm) and graphene powder (8μm) are mixed in an ethanol solvent at a mass ratio of 3:5, and glucose (accounting for 20% of the mass of graphene powder and nano-silicon dispersion) is added at the same time. Then, the mixture is mixed for 1 hour under the action of a sand mill, and then the mixed solution is heated at 65°C under vacuum for solvent recovery. The solid is dried at 60°C in a vacuum drying oven for 12 hours to obtain a silicon / graphene composite precursor. The precursor is ball-milled and mixed with lithium acetate at a lithium salt mass ratio of 0.2% for 20 minutes, and then the mixture is sintered at 650°C in a nitrogen atmosphere for 5 hours to obtain a silicon-carbon composite containing lithium silicate. The composite is ball-milled and mixed with asphalt at a mass ratio of 90:10 for 1 hour, and then the mixture is sintered at 950°C in a nitrogen atmosphere for 2 hours to obtain the final lithium silicate@silicon / graphene composite silicon-carbon negative electrode material. After testing, the negative electrode material has an initial efficiency of 86.2%, a reversible specific capacity of 952 mAh / g, a 1C capacity retention rate of 63%, and a 2C capacity retention rate of 42%.
[0068] Example 2
[0069] Nano-silicon dispersion and graphene powder are mixed in an ethanol solvent at a mass ratio of 3:5, and glucose (accounting for 20% of the mass of graphene powder and nano-silicon dispersion) is added at the same time, and then mixed for 1 hour under the action of a sand mill, and then the mixed solution is heated at 65°C under vacuum for solvent recovery, and the solid is dried at 60°C in a vacuum drying oven for 12 hours to obtain a silicon / graphene composite precursor. The precursor is ball-milled and mixed with lithium acetate at a lithium salt mass ratio of 0.6% for 30 minutes, and then the mixture is sintered at 650°C in a nitrogen atmosphere for 5 hours to obtain a silicon-carbon composite containing lithium silicate. The composite is ball-milled and mixed with asphalt at a mass ratio of 90:10 for 1 hour, and the mixture is sintered at 950°C in a nitrogen atmosphere for 2 hours to obtain the final lithium silicate@silicon / graphene composite silicon-carbon negative electrode material. After testing, the negative electrode material has an initial efficiency of 85.2%, a reversible specific capacity of 945 mAh / g, a 1C capacity retention rate of 77%, and a 2C capacity retention rate of 56%.
[0070] from Figure 1 It can be seen that the surface of the silicon-carbon composite is rounded and presents a spherical structure after granulation, which is conducive to the improvement of the compaction density of the battery pole. From the EDS distribution diagram of silicon elements, it can be seen that the silicon particles are also uniformly distributed in the particles. Figure 1 The three pictures in the middle are scanning electron microscope images of the silicon-carbon composite and the corresponding EDS scanning images of carbon and silicon elements.
[0071] from Figure 2The internal structure of the silicon-carbon composite can be seen in the figure. From the figure, an obvious hollow structure can be seen. It is constructed by silicon / graphene composite sheets. The hollow structure can provide sufficient buffer space for the volume expansion of silicon during the charging and discharging process.
[0072] from Figure 3 It can be seen that lithium elements exist on the particle surface in the form of monovalent lithium ions, which can also indirectly explain the formation of lithium salts in the silicon-carbon composite.
[0073] Figure 4 The spectral data that overlap with the standard peak Li2Si2O3 indicate the formation of secondary lithium silicate salts, and the remaining spectral data correspond to the standard peaks of graphite and silicon, respectively.
[0074] Figure 6 The power-off cycle of the lithium silicate@silicon / graphene silicon-carbon composite negative electrode material prepared in Example 2 is illustrated, indicating that it has a long cycle life.
[0075] Example 3
[0076] The nano-silicon dispersion and graphene powder are mixed in an ethanol solvent at a mass ratio of 3:5, and sucrose (accounting for 5% of the mass of graphene powder and nano-silicon dispersion) is added at the same time, and then mixed for 1 hour under the action of a sand mill, and then the mixed solution is heated at 65°C under vacuum to recover the solvent, and the solid is dried at 60°C in a vacuum drying oven for 12 hours to obtain a silicon / graphene composite precursor. The precursor is ball-milled and mixed with lithium acetate at a lithium salt mass ratio of 1% for 40 minutes, and then the mixture is sintered at 650°C in a nitrogen atmosphere for 5 hours to obtain a silicon-carbon composite containing lithium silicate. The composite is ball-milled and mixed with asphalt at a mass ratio of 90:10 for 1 hour, and the mixture is sintered at 950°C in a nitrogen atmosphere for 2 hours to obtain the final lithium silicate@silicon / graphene composite silicon-carbon negative electrode material. After testing, the negative electrode material has an initial efficiency of 85.8%, a reversible specific capacity of 972 mAh / g, a 1C capacity retention rate of 65%, and a 2C capacity retention rate of 48%.
[0077] Example 4
[0078] The difference from Example 2 is that the precursor and lithium acetate are ball-milled and mixed for 30 minutes according to the lithium salt mass ratio of 0.1%. The obtained lithium silicate@silicon / graphene composite silicon-carbon negative electrode material has an initial efficiency of 85.6%, a reversible specific capacity of 938mAh / g, a 1C capacity retention rate of 56%, and a 2C capacity retention rate of 32%. Compared with Example 2, there is too little lithium salt in Example 4, and the electrochemical performance of the obtained negative electrode material is reduced.
[0079] Comparative Example 1
[0080] Nano-silicon dispersion and graphene powder are mixed in an ethanol solvent at a mass ratio of 3:5, and glucose (accounting for 20% of the mass of graphene powder and nano-silicon dispersion) is added at the same time. Then, the mixture is mixed for 1 hour under the action of a sand mill, and then the mixed solution is heated under vacuum for solvent recovery. The solid is dried at 60°C in a vacuum drying oven for 12 hours to obtain a silicon / graphene composite precursor. The precursor is then sintered at 650°C in a nitrogen atmosphere for 5 hours. The composite is ball-milled and mixed with asphalt at a mass ratio of 90:10 for 1 hour, and the mixture is sintered at 950°C in a nitrogen atmosphere for 2 hours to obtain the final silicon / thin-layer graphite composite silicon-carbon negative electrode material. The first efficiency is 86.5, the reversible specific capacity is 974mAh / g, the 1C capacity retention rate is 41%, and the 2C capacity retention rate is 20%.
[0081] Comparative Example 2
[0082] Nano-silicon dispersion and traditional lithium-ion graphite anode (uncoated graphite anode) are mixed in an ethanol solvent at a mass ratio of 3:5, and glucose (accounting for 20% of the mass of graphite material and nano-silicon dispersion) is added at the same time. Then, the mixture is mixed for 1 hour under the action of sand mill, and then the mixed solution is heated under vacuum for solvent recovery. The solid is dried at 60°C in a vacuum drying oven for 12 hours to obtain a silicon / graphite composite precursor. The precursor is then sintered at 650°C in a nitrogen atmosphere for 5 hours to obtain a silicon-carbon composite. The composite is ball-milled and mixed with asphalt at a mass ratio of 90:10 for 1 hour, and the mixture is sintered at 950°C in a nitrogen atmosphere for 2 hours to obtain the final silicon / graphite composite silicon-carbon anode material. The first efficiency is 87.3%, the reversible specific capacity is 965mAh / g, the 1C capacity retention rate is 40%, and the 2C capacity retention rate is 21%.
[0083] from Figure 5 It can be seen from the comparison that the rate performance of the silicon-carbon negative electrode material of Example 2 is higher than that of Comparative Example 1 and Comparative Example 2.
[0084] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solutions of the present application are within the spirit scope covered by the present application.
Claims
1. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The steps include: 1) mixing graphene powder and nano-silicon dispersion to obtain a mixed solution; 2) heating the mixed solution to remove the solvent to obtain a nano-silicon / graphene precursor composite; 3) mixing the nano-silicon / graphene precursor composite with a lithium salt and grinding them to obtain a mixture; 4) calcining the mixture to obtain a composite material in which the surface of nano-silicon is coated with lithium silicate; 5) The composite material in step 4) is mixed with asphalt and then carbonized and sintered to obtain a nano-silicon / graphene silicon-carbon composite negative electrode material coated with lithium silicate.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: In step 1), the mixing comprises: mixing the nano-silicon dispersion and the graphene powder in a solvent, preferably by sand grinding; and / or, The solvent is selected from one or more of alcohols, methyl pyrrolidone and acetone; the alcohol solvent is selected from one or more of ethanol, isopropanol and butanol; and / or, A carbon source is also added to the solvent, and the carbon source is selected from a mixture of one or more of glucose, sucrose, polyvinyl pyrrolidone, and carboxymethyl cellulose. Preferably, the carbon source accounts for 5-40% of the mass of the graphene powder and the nano-silicon dispersion.
3. The method for preparing the negative electrode material according to claim 1 or 2, characterized in that: In step 2), the heating is performed at 40-65° C. under vacuum.
4. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: In step 3), the lithium salt is selected from one or more of lithium carbonate and lithium acetate; and / or, The lithium salt accounts for 0.2-1% of the mass of the nano-silicon / graphene precursor composite.
5. The method for preparing the negative electrode material according to any one of claims 1 to 4, characterized in that: In step 3), the grinding is ball milling, and the ball milling time is 20-40 minutes.
6. The method for preparing the negative electrode material according to any one of claims 1 to 5, characterized in that: In step 4), the calcination treatment conditions include: sintering for 3-12 hours at 330-700° C. in an inert atmosphere.
7. The method for preparing the negative electrode material according to any one of claims 1 to 6, characterized in that: In step 5), the composite and the asphalt are mixed in a mass ratio of 85:15-98:2, preferably by ball milling.
8. The method for preparing the negative electrode material according to any one of claims 1 to 7, characterized in that: In step 5), the carbonization sintering conditions include: sintering for 1-5 hours in an inert atmosphere at 800-1200°C.
9. A lithium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the negative electrode material according to any one of claims 1 to 8 for making lithium-ion batteries.
Citation Information
Patent Citations
A core-shell graphene-silicon composite material, its preparation method, electrode material, and battery.
CN110112380B
Silicon-carbon anode materials and their preparation methods, lithium-ion batteries
CN111435736B
A secondary doped silicon-based anode material and its preparation method
CN112751011B